Case report: 2-year-old boy with grade 4 avulsion injury of the hand caused by a conveyor belt system = Case report: 2-jähriger Junge mit viertgradiger Avulsionsverletzung der Hand durch Einklemmung in ein Förderband - Deeg, Susanne; Boettcher, Michael; Svoboda, Daniel (Klinische Pädiatrie, 2023)
Thieme E-Books & E-Journals
Artikel online veröffentlicht: 09. September 2022
Gesehen am 17.03.2023